Feasible Cluster Model Method for Simulating the Redox Potentials of Laccase CueO and Its Variant - Jiang, Qixuan; Cui, Ziheng; Wei, Ren; Nie, Kaili; Xu, Haijun; Liu, Luo (Frontiers in Bioengineering and Biotechnology, 2022)
Laccases are regarded as versatile green biocatalysts, and recent scientific research has focused on improving their redox potential for broader industrial and environmental applications. Quantum chemistry study, especially density functional theory (DFT) based calculations of redox potentials, is essential for a better understanding of the relationship between the redox potential and the structural characteristics of laccases. Based on the X-ray crystal structure of wild type (WT) laccase CueO from Escherichia coli and its mutant, a truncated miniature cluster model method was established in this study. The redox potentials are calculated based on the Gibbs free energy change of the redox reaction, with the overall Gibbs free energy change partitioned into the Gibbs free energy change of the gas phase reaction and the Gibbs free energy change of solvation. The trends of redox potentials to increase after mutation predicted by the theoretical calculations correlated well with those obtained by experiments, thereby validating the feasibility of this cluster model method for simulating the redox potentials of laccases.